Tau Imaging in the 4-Repeat-Tauopathies Progressive Supranuclear Palsy and Corticobasal Syndrome: A 11C-Pyridinyl-Butadienyl-Benzothiazole 3 PET Pilot Study. (April 2020) - Schröter, Nils; Blazhenets, Ganna; Frings, Lars; Barkhausen, Christoph; Jost, Wolfgang H.; Weiller, Cornelius; Rijntjes, Michel; Meyer, Philipp T.
Abstract : Background and Objectives: To evaluate tau PET using 11 C-pyridinyl-butadienyl-benzothiazole 3 ( 11 C-PBB3) in the 4-repeat (4R)-tauopathies progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS). Methods: Retrospective analysis of 11 C-PBB3 PET in 2, 7, and 2 patients with CBS, PSP, and Alzheimer dementia (AD), respectively. Normalized 11 C-PBB3 uptake in clusters with significant hypometabolism on 18 F-FDG-PET and corresponding atlas-based volumes of interest was compared between diagnostic groups. Results: In accordance with visually appreciable group differences, 11 C-PBB3 uptake was significantly higher in dorsolateral frontal and motor cortex in CBS patients and frontal and temporal cortices in AD patients as compared with PSP patients. Patients with PSP showed mildly but significantly higher uptake in midbrain compared with AD patients. Conclusions: In line with known neuropathological changes, the spatial pattern and magnitude of 11 C-PBB3 tau binding differ between CBS, PSP, and AD, which may be of diagnostic utility. Thus, 11 C-PBB3 offers a promising lead structure for development of ligands for tau imaging, including 4R-tauopathies. Abstract : Supplemental digital content is available in the text.